CHALLENGES IN DEVELOPING VACCINE FOR CANINE DISTEMPER - AHMAD , MT; HASHMI, HA; HASSAN, MU; KHALIQ, A; SHAH, SKA; MAQBOOL, B; EJAZ, A; JAMIL, S; REHMAN, MU; FRAZ, A (Biological and Clinical Sciences Research Journal, 2024)
The Canine Distemper Virus (CDV) represents a considerable risk to domestic and wild carnivore populations globally, notwithstanding the existence of vaccinations. This study examines the significant obstacles in creating successful CDV vaccines, especially regarding virus evolution, immune evasion, cross-species transmission, and vaccine reluctance. This review aims to consolidate existing research on CDV vaccine development, emphasizing emerging technologies, such as nanoparticle and DNA vaccines, and their capacity to address present challenges in immunogenicity and cross-species protection. Through the analysis of recent findings, this review delineates significant gaps in the comprehension of CDV's genetic variety of CDVs, the sustainability of wildlife reservoirs, and the obstacles to attaining extensive vaccination coverage. This review evaluates the influence of public health infrastructure and socioeconomic factors on vaccination distribution and uptake constraints, particularly in developing areas. These findings highlight the significance of a One Health approach, which amalgamates veterinary, wildlife, and public health viewpoints to address CDV epidemics more efficiently. Future research should focus on augmenting vaccine efficacy in non-domestic species, increasing public awareness of immunization initiatives, and creating thermostable vaccines for improved distribution accessibility. This review offers critical insights into the intricacies of the CDV vaccination and presents a framework for enhancing worldwide initiatives to combat this destructive virus.